PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI BADAN PENGELOLA KEUANGAN DAN PENDAPATAN DAERAH KABUPATEN TANA TORAJA - Situru, Febransa Risfi; Marampa, Adriana Madya; Tammu, Rahma G. (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Organizational Culture and Organizational Commitment are two factors that are believed to determine the performance of human resources in an agency. This research aims to prove whether this also applies to BPKAD Tana Toraja. The population in this study was 74 ASN people at BPKAD. The research was conducted using a quantitative approach. Data collection was carried out using questionnaires and observation instruments. Data were analyzed using multiple linear regression analysis methods, and the results were presented in table form accompanied by narrative. The research results show that both organizational culture and organizational commitment have a significant effect on BPKAD's performance. The author suggests that a healthy organizational culture and strong organizational commitment should always be built to improve institutional performance Keywords: Organizational Culture; Organizational Commitment; Organizational Performance